Genetic variability of Araucaria angustifolia in the Argentinean Parana Forest and implications for management and conservation - Inza, Maria Virginia; Aguirre, Natalia Cristina; Torales, Susana Leonor; Pahr, Norberto Manuel; Fassola, Hugo Enrique; Fornes, Luis Fernando; Zelener, Noga (2018)
The main forces shaping genetic variability of woody species in fragmented forest are the geographical distribution and demographic history of populations. We conducted molecular analyses to evaluate how these factors have affected Araucaria angustifolia genetic variability in the Argentinean Parana Forest and to identify valuable gene pools for conservation and management purposes. Using 706 polymorphic AFLP (Amplified Fragment Length Polymorphism) markers, we analyzed nine native populations with different logging history and one plantation (312 individuals) of an uncertain origin. Average genetic diversity for the native populations was moderate-to-low (He = 0.128) in accordance with their marginal location within Araucaria’s range. In general, genetic diversity of populations decreases from east to west with increasing distances from the main area of species distribution on southern Brazil. Logging may have been responsible for further reduction of genetic variability in the more intensely exploited populations of the southern region and in some private fields. The moderate genetic differentiation among populations (ΦPT = 0.080) suggests an increase in the genetic structure of remnant populations because of fragmentation. UPGMA and Bayesian analyses agreed with the geographic location of populations. Populations from the southern Provincial Parks at Araucaria’s range edges grouped and differed genetically more from other populations. The highest genetic diversity of the plantation (He = 0.155) suggests that its individuals could have originated from seeds collected from different and/or highly variable sources of Brazil and the northeast of Argentina.